The Problem Management of Picky Eating in Preschool Children Based on Complementary and Alternative Therapy - Widia Shofa Ilmiah; Rifzul Maulina; Anik Sri Purwanti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Picky eating is a prevalent issue among preschool children, often leading to nutritional deficiencies, disrupted growth, and increased parental stress. This systematic literature review aims to explore the management of picky eating through complementary and alternative therapies (CAT) and compares these findings with contemporary interventions. Picky eating behaviors can significantly affect children’s eating patterns, leading to challenges in maintaining a balanced diet. Although traditional medical interventions focus on behavioral modification and nutritional counseling, many parents are seeking alternative approaches to manage these behaviors in a more holistic and natural manner. This review encompasses studies published between 2015 and 2025, sourced from PubMed, Scopus, and Google Scholar, using keywords such as "Alternative Therapy," "Picky Eating," and "Preschool Children." The review population consists of 20 articles, and the sample includes 5 selected studies that meet the criteria for evaluating the effectiveness of complementary and alternative therapies in managing picky eating behaviors. Data analysis utilized thematic analysis, with the findings analyzed thematically to draw conclusions regarding the efficacy of CAT. The results indicated that mindfulness practices, dietary practices, Tuina massage as a traditional therapy, taste exposure, sensory learning, and nutrition education were all effective in reducing picky eating behavior among children aged 1 to 5 years. These approaches not only helped to improve children’s acceptance of a wider variety of foods but also contributed to the reduction of stress for both children and parents. The findings suggest that integrating these alternative therapies into conventional practices can provide a comprehensive and effective strategy to address picky eating in preschool children. Future research is needed to further explore the long-term impacts of these therapies and to identify the most suitable combinations for different individual needs.